The Presumption of Advancement in New Zealand: Time to Relegate this Doctrine to the Annals of History - Ye, Ruiping (Victoria University of Wellington Law Review, 2023)
This article is informed by a survey carried out in 2021, which found that the application of the presumption of advancement in New Zealand has been inconsistent, and at times confused, in the past 20 years. Taking the analysis further, this article argues that the doctrine of the presumption of advancement should be abolished in New Zealand for transfers of property by parents to adult children ("parent-child transfers"). The doctrine has become increasingly irrelevant. Most notably, the Land Transfer Act 2017 has implicitly abolished the presumption of advancement as well as the presumption of resulting trust in transfers concerning interests in land. The rationales for the doctrine have also become unconvincing or inapplicable. Parental affection has been a synonym for the parent-child relationship, which was underpinned by the financial status of fathers in a bygone era. In the changed legal and societal context of contemporary New Zealand, the notion that parents owe a moral obligation to provide for able-bodied adult children should not entail legal consequences. Complications with relationship property disputes, protection of the elderly and other considerations also support abolition of the doctrine. This article proposes a presumption of loan instead to give certainty, assist court adjudication and guide public behaviour.